VD_FINDINFO HC / 2016 / 293 vom 21. März 2016 - VD Tribunal cantonal (2016)
EXPULSION DE LOCATAIRE, EXÉCUTION FORCÉE, TACITE, BAIL À LOYER | 1 al. 2 CO, 257d CO, 337 al. 1 CPC (CH), 337 al. 2 CPC (CH)